Production of extracellular tannase enyzme by Aspergillus Niger - Muhamad Syafiq Eidham, Ab Rashid (2012)
Tannase catalyses the hydrolysis reaction of the ester bond present in gallic acid esters and hydrosable tannins.This enzyme is produced by plants and microorganism and used in food industry such as tea industry.In order to produce high yields of tannase enzymes,it needs optimization of parameters which normally consuming a lot of time and expensive to be optimized conventionally.In this study, Response Surface Methodology (Central Composite Design) was performed for optimization.Aspergillus niger had been chosen as biomass and glucose as substrate in this study.The fermentation study was take place in the shake flask and was optimized for higher tannase enzyme activity.There are three factors was studied in this study which are the pH of the fermentation medium (pH 3.5-pH 6.0),the substrate concentration (2 w/v%-10 w/v%) and the agitation speed (100 rpm-300 rpm).From one factor at a time (OFAT) analysis, tannase enzyme showed that the optimum tannase activity at pH 5, 6.0 w/v% and 200 rpm with 14.9521 U/ml, 13.1256 U/ml and 12.4301 U/ml.RSM results shows that the optimum values of each parameter were pH 4.75, 6.0 v/w% of substrates concentration and 200 rpm of agitation speed which resulted the optimum tannase activity at 15.3131 U/ml.As a conclusion,RSM is the best tool used to identify the correlation between controlled independent factors and observed dependent responses.For the future research,it is recommended for study the application of genetic engineering in the enzyme production by scale up tannase production using a bioreactor and toxicology studies on tannase enzyme for application in food industry.